2013
DOI: 10.1093/pubmed/fdt036
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of latent tuberculosis, syphilis, hepatitis B and C among asylum seekers in Malta

Abstract: Systematic screening for asymptomatic migrants in Malta is not recommended for hepatitis C and syphilis, given the low prevalence observed. On the contrary, it should be considered for hepatitis B. TST could be indicated as the first step of a two step screening for migrants from countries with high TB incidence. Efficacy and cost-effectiveness could be achieved by further targeting screening to specific subgroups at higher risk of reactivation, such as people living with HIV and subjects affected by chronic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
2
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 28 publications
3
19
2
2
Order By: Relevance
“…Just 8 studies excluded those with active TB from their study [23,32,34,50,66,68,69,71]. Only 16 studies reported on BCG vaccination with 9 using BCG scar as evidence of vaccination [28,32,33,53,55,58,60,71,72], 5 using BCG self-reporting as evidence [23,29,35,66,69], and 2 using BCG vaccination schedule in country of origin as a proxy for BCG vaccination [48,73], although BCG vaccination rates varied considerably across studies (0-100 %). The characteristics of the 51 included studies are included in Table 1 and in the supplementary text, which summarizes each of the 51 studies included in the review.…”
Section: Resultsmentioning
confidence: 99%
“…Just 8 studies excluded those with active TB from their study [23,32,34,50,66,68,69,71]. Only 16 studies reported on BCG vaccination with 9 using BCG scar as evidence of vaccination [28,32,33,53,55,58,60,71,72], 5 using BCG self-reporting as evidence [23,29,35,66,69], and 2 using BCG vaccination schedule in country of origin as a proxy for BCG vaccination [48,73], although BCG vaccination rates varied considerably across studies (0-100 %). The characteristics of the 51 included studies are included in Table 1 and in the supplementary text, which summarizes each of the 51 studies included in the review.…”
Section: Resultsmentioning
confidence: 99%
“…HBsAg positivity rates were higher among Sub-Saharan migrants, and intermediate among those from East Europe and Northern Africa [15]. In Malta, where most migrants tested were from Somalia, only 31 out of 5000 were found HBsAg positive [20]. Among first generation migrants tested in the Netherlands, the prevalence of HBsAg was estimated to be 3.8%, [22] whereas it was 1.1% among Egyptians [27]; further studies found anti-HBc prevalence ranging from 16.8 to 20%, showing high variability in accordance with age groups and ethnicity [24].…”
Section: Hepatitis B Virusmentioning
confidence: 96%
“…Migration from high-incidence countries (defined as incidence as ≥20 tuberculosis (TB) cases/100,000 inhabitants/year) is known to contribute notably to TB burden in low-incidence countries (<20 TB cases/100,000 inhabitants/year) using the thresholds previously proposed by the Wolfheze working group [4] and adopted in the EU monitoring framework [5] [6][7][8][9][10][11][12][13][14]. Persons with latent TB infection as well as patients with active TB and multidrug-resistant (MDR) TB can easily move from one country to another in the EU.…”
Section: Introductionmentioning
confidence: 99%